A Bank for Curiosity (2009)
As in a school of fish, the questions of EAFIT Children's University form schools according to their characteristics, for example, there are questions about humankind, nature and technology. And, as in a blood bank, there are those who collect them, can analyze them, preserve them, test them and then transmit them.